Consequences of a high incidence of microsatellite instability and BRAF‐mutated tumors: A population‐based cohort of metastatic colorectal cancer patients - Kristine Ø. Aasebø; Anca Dragomir; Magnus Sundström; Artur Mezheyeuski; Per‐Henrik Edqvist; Geir Egil Eide; Fredrik Ponten; Per Pfeiffer; Bengt Glimelius; Halfdan Sorbye (Cancer Medicine, 2019)
Abstract Background Immunotherapy for patients with microsatellite‐instable (MSI‐H) tumors or BRAF‐inhibitors combination treatment for BRAF‐mutated (mutBRAF) tumors in metastatic colorectal cancer (mCRC) is promising, but the frequency of these molecular changes in trial patients are low. Unselected population‐based studies of these molecular changes are warranted. Methods A population‐based cohort of 798 mCRC patients in Scandinavia was studied. Patient and molecular tumor characteristics, overall survival (OS) and progression‐free survival (PFS) were estimated. Results Here, 40/583 (7%) tumor samples were MSI‐H and 120/591 (20%) were mutBRAF; 87% of MSI‐H tumors were mutBRAF (non‐Lynch). Elderly (>75 years) had more often MSI‐H (10% vs 6%) and MSI‐H/mutBRAF (9% vs 4%) tumors. Response rate (5% vs 44%), PFS (4 vs 8 months), and OS (9 vs 18 months) after first‐line chemotherapy was all significantly lower in patients with MSI‐H compared to patients with microsatellite stable tumors. MSI‐H and mutBRAF were both independent poor prognostic predictors for OS (P = 0.049, P < 0.001) and PFS (P = 0.045, P = 0.005) after first‐line chemotherapy. Patients with MSI‐H tumors received less second‐line chemotherapy (15% vs 37%, P = 0.005). Conclusions In unselected mCRC patients, MSI‐H and mutBRAF cases were more common than previously reported. Patients with MSI‐H tumors had worse survival, less benefit from chemotherapy, and they differed considerably from recent third‐line immunotherapy trial patients as they were older and most had mutBRAF tumor (non‐Lynch).